Penerapan Payment Gateway pada Aplikasi Marketplace Waroeng Mahasiswa Menggunakan Midtrans - Al Fian; Petrus Sokibi; Lena Magdalena (Jurnal Informatika Universitas Pamulang, 2020)
Catur Insan Cendekia University is one of the universities in Cirebon City which is based on technology and management. As an educational institution that has a technopreneur campus slogan, many Catur Insan Cendekia University students have implemented entrepreneurship courses and have developed into new entrepreneurial owners scattered on various social media. However, due to limited space and marketing reach in the campus area, many academicians do not see the product / service offerings made by Catur Insan Cendekia University students. So a work program called Waroeng Mahasiswa was launched by BKM CIC with the aim of being a space for students to market their products / services in the Catur Insan Cendekia University campus area. The Waroeng Mahasiswa work program will be developed into a web-based marketplace application made using the PHP programming language. This marketplace application will also be equipped with an online payment system that is integrated with Midtrans as a payment gateway service provider to make the transaction process faster, easier and more practical.